Epidemiology and diagnosis of attention deficit hyperactivity disorder in the Arab and Jewish populations in Israel - Jaber, Lutfi; Hamed, Nasrin; Grossman, Ephraim S; Berger, Itai (Archives of Community Medicine and Public Health, 2020)
Aims: The aims of our study were to understand the factors shaping the gap in the literature concerning the Israeli Arab population, and to enhance the knowledge of Attention Deficit Hyperactivity Disorder (ADHD) among this population, and provide information to health professionals. Methods: Retrospective data was collected from medical records in outpatient clinics between the years 2005-2017. Data included 474 Arab and 292 Jewish children aged 5 to 18 years. Results: Main reason for referral was inattention symptoms (44.4%) in Arabs, and academic problems (42.8%) in Jews. Arab preschoolers were mainly hyperactive, whereas adolescents complained about academic difficulties. Arab girls reported inattention symptoms, whereas boys complained of aggressive behavior. ADHD combined subtype (ADHD- C) was the most common subtype in both populations. ADHD-C was more prevalent in preschoolers, and ADHD Inattentive subtype (ADHD-I) was more prevalent between ages 11.1 to 15 years. We found an association between language delay and ADHD in both populations. Conclusion: ADHD characteristics among Israeli Arab and Jewish populations were mainly similar, and analogous with global results.